"Phantom of the Opera" or "Sex and the City"? – Historical Amenities as Sources of Exogenous Variation - Thomas K. Bauer; Philipp Breidenbach; Christoph M. Schmidt (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2014)
Using the location of baroque opera houses as a natural experiment, Falck et al. (2011) claim to document a positive causal effect of the supply of cultural goods on today's regional distribution of talents. This paper raises serious doubts on the validity of the identification strategy underlying these estimates, though. While we are able to replicate the original results, we proceed to show that the same empirical strategy also assigns positive causal effects to the location of historical brothels and breweries. These estimated effects are similar in size and signifi cance to those of historical opera houses. We document that all these estimates reflect the importance of institutions for long-run economic growth, and that the effect of historical amenities on the contemporary local share of high skilled workers disappears upon controlling for regions' historical importance. – – Anhand der Standorte barocker Opernhäuser als natürliches Experiment zeigen Falck et al. (2011) einen positiven kausalen Effekt zwischen dem regionalen Angebot an Kulturgütern und der Verteilung talentierter Personen. Dieses Papier wirft allerdings Schwächen in der angewandten Identifikationsstrategie auf. Während die Originalergebnisse replizieren werden können, zeigen wir, dass diese Identifikationsstrategie ebenso positive Effekte für die Standorte von Bordellen und Brauereien der Barockzeit liefert, die in Größe und Signifikanz denen der Opern sehr ähneln. Mit der Einbeziehung von Verwaltungssitzen und Großstädten der Barockzeit zeigen wir, dass die Ergebnisse die Wichtigkeit der Institutionen widerspiegeln. Die Effekt der anderen historischen Gegebenheiten verschwinden, wenn für die institutionelle Wichtigkeit kontrolliert wird.
Keywords: R11; H42; J24; 330; human capital; historical amenities; regional competiveness